The Effectiveness of English Podcast for Fourth Semester Students’ Listening Ability at Universitas Bhinneka PGRI - Yulia Nugrahini; Karina Rahmadhani (STKIP PGRI Trenggalek, 2021)
In this study, the researcher tested the effectiveness of the English Podcast on fourth-semester students in the English Education Study Program Universitas Bhinneka PGRI academic year 2019/2020. The purpose of this study is to find out whether the use of English podcasts is effective in improving their listening abilities. This research is a quantitative study using a survey method conducted in the English Language Study Program Universitas Bhinneka PGRI academic year 2019/2020. The population in this study was the fourth-semester students of the English Education Study Program Universitas Bhinneka PGRI in the academic year 2019/2020. The research sample was all B class students, a total of 15 students were taken by purposive sampling technique. To collect data, the researcher used a questionnaire as a research instrument that was shared online through Google Classroom. The data obtained are then calculated and analyzed using a Likert Scale. And the results state that the highest score is 57 and the lowest score is 40. The result of hypothesis analysis calculated using IBM SPSS Statistics 24 using the Mann-Whitney formula shows that a significant value (2-tailed)> 0.05, which means H0 is accepted and H1 is rejected. It can be seen that 0.531> 0.05. Thus, it can be concluded that the use of English podcasts does not make a significant difference in students who listen to those who do not listen. But podcasts can still be used as a variety of media to improve the listening skills of fourth-semester students because they have a variety of benefits. Such as the material discussed by a Podcast not only presents general information but also from another perspective